A colour handbook of dermatology - Rycroft, Richard J. G. (Manson, 2010)
This book combines the advantages of a color atlas with those of a concise textbook, and details the essential features of all but the very rarest skin diseases. The book provides the definition of each disease/disorder, clinical features, epidemiology, differential diagnosis, investigations and special points. Every opportunity is taken to illustrate variations in conditions that occur with age or racial group.